Impact of Group Dynamics on Team - Naveenan, R.V. Naveenan; Kumar, B. Ravi (American International Journal of Social Science Research, 2018)
After a brief review of integrative small group learning models that have appeared in the educational psychology literature, this article then looks into the group dynamics literature and describes one of that field’s most well-documented findings: that interactions among group members change somewhat predictably over time. How theorists from various traditions within educational psychology might explain and explore the phenomenon of “group development” is proposed, followed by a description of the theoretical and practical features of an increasingly popular post-secondary instructional strategy designed to stimulate group development and leverage it to instructional ends. So group dynamics can be called as a life base of a team. So in this study the researcher has conducted a study on various aspects of group dynamics. The researcher has collected data using collection techniques and has used various tools to analyze the outcomes to get considerable results.